2018
DOI: 10.3390/land7040125
|View full text |Cite
|
Sign up to set email alerts
|

Regional Socioeconomic Changes Affecting Rural Area Livelihoods and Atlantic Forest Transitions

Abstract: Centuries of colonization of the Atlantic Forest biome in Brazil have led its native vegetation cover to be reduced to only 11.7%. On the other hand, regional land changes have fostered natural forest regeneration, since the 1960s, in the region of Paraíba Valley. A fieldwork survey in rural properties was conducted in three municipalities (n = 90, thirty in each municipality), to assess how forest transition is affected by the region’s socioeconomic development and biophysical dimensions of the landscape. To … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 49 publications
1
7
0
1
Order By: Relevance
“…Previous studies in the Atlantic Forest have also demonstrated that socioeconomic changes from the 1960s onward (i.e., industrialization) triggered the emergence of large urbanized areas (i.e., built-up class-significant and positively correlated with forest net gain, Figure 3) followed by a sharp rural out-migration process (Baeninger, 2005;Teixeira, 2005;Silva et al, 2017a). This phenomenon is attributed by landowners in the São Paulo Atlantic Forest as a reason for the lack of rural labori.e., a major factor for land abandonment and the return of NFC (Silva et al, 2018). Our Supplementary data (SM-Supplementary model) also shows that in the FT group during the 2001-2015 period, industrial GDP growth was positively associated with NFC net gain, which supports an economic development pathway of the forest transition theory.…”
Section: Human-environment Dimensions Of Forest Transition In the Atl...supporting
confidence: 71%
“…Previous studies in the Atlantic Forest have also demonstrated that socioeconomic changes from the 1960s onward (i.e., industrialization) triggered the emergence of large urbanized areas (i.e., built-up class-significant and positively correlated with forest net gain, Figure 3) followed by a sharp rural out-migration process (Baeninger, 2005;Teixeira, 2005;Silva et al, 2017a). This phenomenon is attributed by landowners in the São Paulo Atlantic Forest as a reason for the lack of rural labori.e., a major factor for land abandonment and the return of NFC (Silva et al, 2018). Our Supplementary data (SM-Supplementary model) also shows that in the FT group during the 2001-2015 period, industrial GDP growth was positively associated with NFC net gain, which supports an economic development pathway of the forest transition theory.…”
Section: Human-environment Dimensions Of Forest Transition In the Atl...supporting
confidence: 71%
“…The urban expansions usually prefer greenfield locations, assuming both lower land prices and lower servicing costs [59]. In another case, urban pressure seems to be influenced by political decisions [63,64]. The spatial development policy in the peri-urbanisation area-as an outcome of the decision-is believed to be the right decision for urban regeneration due to depressed main cities and their suburban areas [64].…”
Section: Large-scale Land Development and Driving Forces Of Urbanisation Pressurementioning
confidence: 99%
“…This regional market is a key source of income for dairy producers but also to maintain other rural practice (e.g., livestock and agriculture) that has deep cultural roots in the valley's history [57]. Although its participation is 14% of the dairy production in São Paulo State, the region suffers a labor loss which jeopardies the maintenance of dairy and other rural practices because of the competitive pressure from the developed urban regions of the valley where wages, labor rights, and amenities (e.g., schools, hospitals) are more attractive to younger generations than in rural areas [58]. While in several cases smallholders sell agricultural products as goods into the regional and international markets, there are also cases that agricultural products are shared between rural smallholders and their relatives dwelling in urban areas (No.…”
Section: How Do Smallholders Connect To Other Systems?mentioning
confidence: 99%